Chef Wan's sweet treats - Redzuan Ismail (Times Editions, 2000)
From Malaysia's most popular food ambassador Chef Wan comes this compilation of over 200 dessert and pastry recipes. This exciting collection ranges from delectable tarts and muffins to fragrant breads and puddings. Choose from all-time favourites like Chocolate Brownies, English Trifle and All-American Pie, and innovative delights such as Foccaccia with Red Onion and Rosemary, Persimmon Cake and Durian Cheesecake. With Chef Wan's delightful recipes, entertaining personal anecdotes and baking secrets, this fun and informative book will inspire anyone who enjoys creating special treats for family and friends.